Applied Nuclear Physics электронный курс - Святкин физик доцент Томского политехнического университета, Кандидат физико-математических наук; Степанова физик доцент Томского политехнического университета, кандидат технических наук; Малютин физик старший преподаватель Томского политехнического университета; Крючков физик профессор Томского политехнического университета, доктор физико-математических наук (TPU Moodle, 2020)
The course is aimed at training specialists able to present key questions in the theory of the radiation interaction with matter; form skills and possession of experience in the field of elemental and structural analysis of the surface and surface layers of solids by nuclear physics methods. The course goals are in compliance with the goals of the master degree program within 03.04.02 Physics